The gonadotropin-releasing hormone (GnRH) system: a comparison between breeding and non-breeding naked mole rats (Heterocephalus glaber) - Smith, Caitlin (Department of Biological Sciences, 2014)
Neuropeptides are well known to govern numerous biological functions and are found in all phyla studied to date. Probably the best known neuroendocrine system is the hypophyseal-portal system found in vertebrates, and one of the functions of this system is to mediate reproduction. Mammalian reproduction is controlled by a hormonal cascade which begins in distinct brain regions, namely the hypothalamus and the pituitary gland. Gonadotropin-releasing hormone (GnRH) is a neuropeptide typically produced in the hypothalamus. It is the key neuropeptide for initiating this cascade, and without it, reproduction cannot occur. Naked mole rats (Heterocephalus glaber) have a rigid social hierarchy. The "queen" is the most dominant female and is the only female who breeds. All aspects of reproduction are suppressed in other females in the colony: these "subordinates" are in a prepuberty-like state as they do not ovulate or display breeding behaviours. They are, however, not infertile, and are capable of rising to the breeding position. Since GnRH is the "master hormone" of reproduction, this study investigates its role in the socially-induced suppression of reproduction in female H. glaber. Brains of breeding (n = 7) and non-breeding (n = 5) female naked mole rats were compared to determine any differences in brain size, particularly in regions related to GnRH production. Noteworthy morphological and physiological transformations accompany the change from subordinate to dominant social status, including a significant increase in body length (Mann Whitney U test; p = 0.005, U = 0.000), body mass (Mann Whitney U test; p = 0.009, 1.000) and pituitary width and length (Mann Whitney U test; p = 0.028, U = 0.500 and p = 0.018, U = 0.000, respectively). Since little is known about the GnRH system in H. glaber, this study used immunocytochemistry to identify the distribution and abundance of GnRH neurons in the brains of both breeding and non-breeding females. GnRH neurons were found in the median eminence of the hypothalamus and in the anterior pituitary of both queens and subordinates, however in the brain of queen (n = 7) naked mole rats, there is a significantly larger area of immunoreactivity in comparison to the subordinate (n = 5) brain tissue (Mann Whitney U = 4.000, p = 0.030). This suggests that, in , subordinates, GnRH is inhibited at the level of production. The amino acid structure of the form of GnRH found in the brain of the naked mole rat is currently unknown, therefore a pilot study was carried out, using synthetic mammalian GnRH (mGnRH), mouse brain tissue and naked mole rat pituitaries and hypothalami, to examine and modify (where necessary) the methodologies used for neuropeptide extraction, purification and identification. A limited number of naked mole rats were available as source tissue (n = 4), therefore this study also tested whether it is possible to extract and purify an unknown neuropeptide from only a few mammalian samples. Training for reverse-phase liquid chromatography (RP-HPLC) was achieved by practicing the necessary methods with crude extracts prepared from stick insect (Carausius morosus) corpora cardiaca, which also served to compare vertebrate and invertebrate neuroendocrine systems. Synthetic mGnRH was used to demonstrate repeatability of the protocol and to set up suitable conditions for elution of mGnRH: mGnRH elutes at â 12 min when a solvent gradient of 32 % - 47 % B is applied. Synthetic mGnRH was also used to establish the amount of peptide required for accurate identification of GnRH by antigenicity tests (ELISA) and mass spectrometry. However, when extracts of mouse or naked mole rat brain matter were applied to this system, purification of GnRH was unconvincing as either there was insufficient material, or, some endogenous factor was masking the GnRH. Future studies would benefit from using molecular techniques as they require smaller amounts of source tissue. Alternatively, a larger amount of source tissue would be necessary in order to proceed with biochemical studies. While the impaired production of GnRH in subordinate naked mole rats seems to be linked to their prepuberty like state, it is unlikely that GnRH is the sole factor involved. Many other hormones (such as kisspeptin, gonadotropin-inhibiting hormone and neuropeptide Y) may influence GnRH and sexual maturity, and future studies would benefit from a multi-layered approach to investigate suppression of reproduction in naked mole rats.